2021
DOI: 10.1002/acm2.13144
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric impact of the positioning variation of tumor treating field electrodes in the PriCoTTF‐phase I/II trial

Abstract: PurposeThe aim of the present study based on the PriCoTTF‐phase I/II trial is the quantification of skin‐normal tissue complication probabilities of patients with newly diagnosed glioblastoma multiforme treated with Tumor Treating Field (TTField) electrodes, concurrent radiotherapy, and temozolomide. Furthermore, the skin‐sparing effect by the clinically applied strategy of repetitive transducer array fixation around their center position shall be examined.Material and MethodsLow‐dose cone‐beam computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Then, they calculated the dose of radiotherapy plans with and without TTFields arrays of actual cases based on MV-CT and found that there were no clinically signi cant differences in target coverage and OAR sparing between the two groups. There were also some subsequent calculation-based studies [12][13][14][15] reaching a conclusion similar to that of Straube.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Then, they calculated the dose of radiotherapy plans with and without TTFields arrays of actual cases based on MV-CT and found that there were no clinically signi cant differences in target coverage and OAR sparing between the two groups. There were also some subsequent calculation-based studies [12][13][14][15] reaching a conclusion similar to that of Straube.…”
Section: Discussionmentioning
confidence: 67%
“…The metal artifacts caused by TTFields electrodes on kV-CT make it di cult to calculate the dose in the presence of electrodes in kV-CT. Straube et al focused on the calculation-based deep-site dosimetry in glioblastoma radiotherapy with concurrent TTFields [11][12][13][14][15] , which were either based on MV-CT or arti cially assigned electrode HU in kV-CT (3817 or 3832, etc.). However, there is a lack of uniform standard and solid basis for the assignment of electrode HU in these calculation-based researches.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the prediction algorithm for skin irritation probability was presented. According to it, the variation of array positioning reduced the risk of skin irritation by about one-third ( 33 ). Moreover, practical suggestions for dermatological symptomatic treatment have been distributed ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, TTFields has been approved by the FDA for the treatment of rGBM as monotherapy, nGBM in combination with adjuvant chemotherapy, and malignant pleural mesothelioma in combination with chemotherapy ( Stupp et al., 2012 , 2015 , 2017 ; Ceresoli et al., 2019 ). Additionally, TTFields is safe, and the most common side effect that was observed in vivo and in various clinical trials was mild to moderate dermatitis underlying the electrode transducer arrays, which can be managed with slight repositioning of the arrays or topical corticosteroids ( Salzberg et al., 2008 ; Stupp et al., 2012 , 2015 , 2017 ; Pless et al., 2013 ; Mrugala et al., 2014 ; Kesari et al., 2017 ; Zhu et al., 2017 ; Taphoorn et al., 2018 ; Vergote et al., 2018 ; Ceresoli et al., 2019 ; Lu et al., 2019 ; Rivera et al., 2019 ; Bokstein et al., 2020 ; Lacouture et al, 2020 ; Shi et al., 2020 ; Song et al., 2020 ; Wu et al., 2020 , 2021 ; Kim et al., 2020a ; Nour et al., 2021 ). Due to the survival benefits and minimal side effects of TTFields observed in clinical trials thus far ( Supplementary Table S4 ), additional pre-clinical investigations and clinical trials are currently underway with an aim to understand the efficacy of this novel therapeutic modality in various cancer types including nGBM and NSCLC brain metastases in pediatric and adult patients ( Johnson et al., 2017 ; Lau et al., 2017 ), hepatocellular carcinoma, pancreatic cancer, ovarian cancer, malignant pleural mesothelioma, and gastric adenocarcinoma ( https://www.novocure.com ).…”
Section: Perspectivesmentioning
confidence: 99%